Zirconia needles synthesized inside hexagonal swollen liquid crystals - dos Santos, E. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Prouzet, E. (Amer Chemical Soc, 2004)
We report the synthesis of zirconia microneedles by the direct nucleation of particles inside a hexagonal swollen liquid crystal (SLC) (cell parameter a = 27 nm) prepared by mixing with the proper ratio, an aqueous solution of sulfated zirconium colloids, a cationic surfactant (cetylpyridinium chloride), cychlohexane as swelling agent with an oil over water ratio of 2.5 (vol.), and 1-pentanol as cosurfactant. After a slow crystallogenesis that can be enhanced by an initial induction step under moderate temperature, particles in the centimeter range can be obtained, with a very high shape ratio (over 100). These particles are made of crystalline octahydrate zirconium oxychloride containing pores of 20 nm diameter, aligned along the main axis of the liquid crystal, as the fingerprint of the oil cylinders present in the hexagonal phase. The morphology of these particles confirms that the shaping mechanism is based on true liquid crystal templating (TLCT). Further thermal treatment of these particles, after extraction from the SLC, leads to the crystallization of zirconia with the same needlelike morphology as the zirconium oxychloride.